Antigenicity and immunogenicity of Rotavirus VP6 rrotein expressed on the surface of Lactococcus lactis - Esteban, Laura Emilia (2013)
Group A rotaviruses are the major etiologic agents of acute gastroenteritis worldwide in children and young animals. Among its structural proteins, VP6 is the most immunogenic and is highly conserved within this group. Lactococcus lactis is a food-grade, Gram-positive, and nonpathogenic lactic acid bacteria that has already been explored as a mucosal delivery system of heterologous antigens. In this work, the nisin-controlled expression system was used to display the VP6 protein at the cell surface of L. lactis. Conditions for optimal gene expression were established by testing different nisin concentrations, cell density at induction, and incubation times after induction. Cytoplasmic and cell wall protein extracts were analyzed by Western blot and surface expression was confirmed by flow cytometry. Both analysis provided evidence that VP6 was efficiently expressed and displayed on the cell surface of L. lactis. Furthermore, the humoral response of mice immunized with recombinant L. lactis was evaluated and the displayed recombinant VP6 protein proved to be immunogenic. In conclusion, this is the first report of displaying VP6 protein on the surface of L. lactis to induce a specific immune response against rotavirus. These results provide the basis for further evaluation of this VP6-displaying L. lactis as a mucosal delivery vector in a mouse model of rotavirus infection.